Reflecting on the teaching/ learning process in a nursing laboratory - Gomes, Cleide Oliveira; Farias, Glaucea Maciel de; Brito, Rosineide Santana de; Torres, Gilson Vasconcelos; Germano, Raimunda Medeiros (Rev Rene, 2005)
The present paper is a bibliographic research related to the teaching in the nursing laboratory in order to identify its contribution to the teaching/learning process, analyzing also its importance in this process. This historic review regarding nursing teaching techniques, has confirmed that such process has always been carried out in the nursing laboratory. The new studies on this theme not only reinforce the idea, but also point towards changes in such teaching, emphasizing the importance of reflective acting, permeating know-how in a scientific and humanizing form. As they reflect upon the learning/teaching process, the analyzed authors reinforce that the less stressful the environment of the nursing laboratory is, the lower the student’s level of stress, as it is the most adequate place for overcoming difficulties, making learning easier and enabling the articulation between theory and practice, knowing and doing, allowing a greater proximity between the subject who learns and the object to be learned.